Efektifitas Insektisida Nabati Laseki Dan Perangkap Likat Dalam Pengendalian Hama Pengorok Daun, Liriomyza Chinensis (Diptera: Agromyzidae) Pada Tanaman Bawang Merah Lokal Palu - Roziyanto, Chandra; A, Shahabuddin; Nasir, Burhanuddin (AGROTEKBIS, 2013)
Onion (Allium ascalonicum L.) is one of the commodities that potential especially in the city of Palu. However, in cultivation, red onions have a lot of problems especially L.chinensis pests. The purpose of this study was to determine the effectiveness of using yellow sticky traps and pesticides in controlling plant LASEKI L.chinensis the crop shallot Local Palu. This study uses a randomized block design tersiri of 2 factors and repeated 4 times. The first factor is the concentration of insecticide LASEKI plant consisting of 3 levels ie: L0 = no LASEKI vegetable insecticides, L1 = 5%, L2 = 10%. The second factor is the use of traps consisting of 2 levels ie P1 = use yellow sticky traps, P2 = The use of transparent sticky traps. Based on those two factors, the obtained 6 treatment combinations with 4 times as many replications. Each treatment there were 10 clumps, so there are 240 family units experiment. The results showed that there was no interaction between treatment sticky traps (P) with botanical pesticides LASEKI the number and amount of imago L.chinensis were caught on sticky traps. Treatment with vegetable insecticide concentration LASEKI 5% (L1) and 10% (L2) is effective in suppressing the number korokan L. chinensis and also effectively increases the production of onion crop. The use of yellow sticky traps (P1) effectively reduces the number of L. chinensis who snore leeks.